Outsourcing the Governing of Education: The Contemporary Inspection of Schooling in England - Lawn, Martin (2014)
The schools inspection service in England has been privatised and private companies manage it, through contracts. These companies hire flexible and part time inspectors who may be led by a small number of permanent HM inspectors. This shift in the highly regulated inspection service has introduced new methods of operation, market based behaviours and commercial confidentiality into the education sector and contrasts with the older, elite, judgement-based advisory work of their predecessors. Knowledge is produced and used by new actors for new purposes. The outsourcing of school inspection is a significant step in governing education, and indicates a future development in its governing knowledge.